(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article discusses the advantage of behavioral methods in the field of corporate finance by examining three main variables: personal traits (Narcissism, psychopathy, and Machiavellianism) as an independent variable, financing decisions as a dependent variable, and finally emotional biases as an intermediary variable. This approach provides a different perspective from traditional rationality theories and allows for an analysis that can fill some of the gaps related to the financing structure of the company. In addition, this study aims to find a framework for reading the personal traits of managers and knowing their impact on financing decisions through emotional biases.